Design and determination of the psychometric properties of a fear of childbirth tool for Iranian adolescent mothers: An exploratory sequential mixed method study protocol - Bibi Leila Hoseini; Abbas Ebadi; Ali Mashhadi; Mohammad Hassan Rakhshani; Raheleh Babazadeh (PLoS ONE, 2025)
Introduction Fear of childbirth (FOC) is a crucial health issue during pregnancy and childbirth, especially among adolescent mothers. Despite emotional, physical and psychological complications of fear of childbirth, perinatal fear and anxiety have been neglected in practice. One reason is the lack of appropriate tools for timely measurement of fear in different target groups. Therefore, researchers have decided to design a fear of childbirth tool and determine its psychometric properties for Iranian teenage mothers on the basis of the cognitive vulnerability model. Methods and analysis This exploratory sequential mixed method study will be conducted in two qualitative and quantitative phases. In the qualitative phase, qualitative content analysis is performed on the basis of the cognitive vulnerability model (CVM) via interviews with pregnant adolescent women and up to 6 months after delivery. The data are analyzed according to Elo and Kyngas (2008) in three steps: preparation, organization and reporting. The quantitative phase of the study will be performed in two parts: tool design and psychometrics. We develop the FOC tool according to Waltz et al. (2017). The first step is to select a conceptual model that will be used from the results of the first phase (qualitative method). The next steps include explicating the objectives for the measure, developing the blueprint, and constructing the measure. The psychometrics of the tool will be determined via validity, including content, face and construct validity (exploratory and confirmatory factor analysis), reliability (internal consistency and relative reliability) and responsiveness. Conclusion Since there is no specific FOC tool for adolescents and the probability of this group being more vulnerable to childbirth, it is necessary to develop a valid tool specifically for adolescents to assess fear of childbirth.